Answer: D
Step-by-step explanation:
If we substitute -12 into this equation we get:
![-3[-12-8]+1.5](https://tex.z-dn.net/?f=-3%5B-12-8%5D%2B1.5)
![-3[-20]+1.5](https://tex.z-dn.net/?f=-3%5B-20%5D%2B1.5)
Because -20 is in absolute value, we simply just use 20.
Thus,
![-3(20)+1.5\\= -60+1.5\\= -58.5](https://tex.z-dn.net/?f=-3%2820%29%2B1.5%5C%5C%3D%20-60%2B1.5%5C%5C%3D%20-58.5)
J(x) is equivalent to Y. For example if you were to have a equation in slope intercept form it would be y=mx+b which can be written in the same way as your problem j(x)=mx+b. To sum it up j(x) is just another way to say y=
Answer:
x=14/3
Step-by-step explanation:
5x-y=6
+ -2x+y=8
----------------
5x+(-2x)-y+y=6+8
5x-2x-y+y=6+8
3x=14
x=14/3
I apologize if something is incorrect, please me know how to fix it. Thank you!
X=0 is definitely the answer but I belive how u solve it is 7×X=0 and that leaves -4 because it would be 0-4 so u just take out the zero. I think, but the answer is 0.